PENGARUH SIKAP TENAGA MEDIS DAN SARANA FASILITAS TERHADAP JUMLAH KUNJUNGAN PASIEN POLI GIGI RUMAH SAKIT TIPE C (Studi terhadap Rumah Sakit Umum dr. R Soetijono Kabupaten Blora dan Rumah Sakit Umum Daerah Ungaran Kabupaten Semarang Jawa Tengah) - Giftarizkipradhani H; Gunawan Wibisono; Aning Susilowati; Farichah Hanum (Jurnal Medali, 2013)
Health development is the most important part from national development and has purpose increasing people awareness to live healthy. Hospital visit indicates people awareness about their health. The purpose of this research are to know the effect on dental staff behavior and facility toward number of patient visit in dental polyclinic hospital type C with different area (RS. dr. R Soetijono Kabupaten Blora and RSUD Ungaran Kabupaten Semarang).The research’s type was analytical observational with cross sectional method. Research’s population was all outpatients in dental polyclinic hospital type C (RS. dr. R. Soetijono Kabupaten Blora and RSUD Ungaran Kabupaten Semarang) with 30 sample for each hospital. Questionnaire is a measure instrument of the research.The result showed that there was no difference in patient perception towards dental staff behavior and hospital facilities in Hospital type C, and also there was no difference number of patient visit in each hospital. On the other hand, there was 41,8% effect on dental staff behavior and facility toward number of patient visit dental polyclinic in hospital type C. Dental staff behavior was more effective than facility toward number of patient visit in hospital type C. Keywords : Dental staff behavior, facilities, number of patient visits dental polyclinic, general hospital type C.